Perancangan Aplikasi Pemesanan Catering Berbasis Web Pada Cafe D’Carlos - Rayhan Fauzan; Irmayani Pawelloi; Untung Suwardoyo; Muhammad Basri; Marlina (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
The development of information technology has affected a large number of sectors, one of which is the culinary industry, namely Cafe D'Carlos located in Parepare. This cafe has problems with the manual catering ordering process due to impracticality, recording errors, and long processing times. This study aims to design and develop a web-based catering ordering application to improve operational efficiency and service quality. In general, the development method for various applications tends to be the same depending on the case being handled. The method used includes several stages, namely: literature study, observation, system design using UML, implementation with PHP programming language and testing with the black box method. The features available in this application consist of main features including user registration, menu package selection, online ordering, payment, order and data management by the admin. The results of the application testing indicate that the system has run according to its function, namely it can reduce frequent order compliance, speed up the ordering process and increase customer satisfaction.